PENGEMBANGAN LEMBAR KERJA HIDROPONIK BERBASIS PROJECT BASED LEARNING UNTUK MENUNJANG JIWA KEWIRAUSAHAAN PADA SISWA - Ayu Tia Sari; Usman Usman; Pipit Marianingsih (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2022)
This research aims to develop practicum worksheet based on Project Based Learning as mean as to support the entrepreneurial spirit of students and to determine the feasibility of the media through expert tests and user response tests. This research was conducted in October 2021-January 2022. The method used in this research was Research and Development (R&D) with a 3D model which consist of define, design and develop. The data collection used at the define stage were questionnaire analysis of the early-late analysis, student analysis, task analysis, concept analysis, and specification of learning objectives. The data collection obtained in the design stage were selecting the media, selecting the format and planning the first product design in form of storyboards, then data collection carried out at the develop stage is media feasibility assessment questionnaire by experts in terms of material and media. The results of the product assessment by material experts obtained an average value of 96,9%, while by media experts it was 97,4%. The results of the user response test obtained an average value of 85.2%. Based on the result of product assessment by experts and user respond test showed that the hydroponic practicum worksheet based on Project Based Learning obtained a very feasible category to be used as a practical guided that could support the entrepreneurial spirit of students